An Analysis of Relationship of Jatakamala and Jataka Appearing in Pali and Commentary - Kaeodueng, Phramaha Komon (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
This article aimed 1) to study the historical background of the Jatakamala and Jataka, 2) to analyze the literary value, 3) to analyze the social value, and 4) to utilize the acquired knowledge for the development of Buddhist academic works and society. The study’s findings are as follows: 1) Jatakamala is related in terms of content to Jataka in the Pali Tipitaka and its commentaries. It is possible that Aryasura might have borrowed content from Jataka in the Tipitaka but with an emphasis on moral teaching. 2) The literary value in all three Jatakas, there found beauty in terms of rhetoric, and a taste of elegance, even in character placement and refinement of words to completely evoke the aesthetic essence. 3) The social value involves the ethical principles found in Jataka which promote morality, and cultural values in Thai society. It includes virtues such as the fidelity of wives to husbands, humility, confidence in Kamma, the existence of heaven, the virtues for perfection accumulation of the Bodhisatta were emphasized to highlight the Buddha’s perfection performance focusing on the Bodhisatta’s behavior as hero which encourages the readers to develop themselves and society for peace and happiness, and 4) The application of acquired knowledge designed to develop people is, for example, the harm of alcohol consumption seen abundantly in the present, Dhamma performance such as precept observing with truthful utterance with supporting patience, requires a strong mind for accomplishing morality, truthfulness, and patience as observed intentionally, which results in the successful outcomes as wished. Any required organizations would implement these virtues to prevent and treat alcohol-related diseases etc.